Job history, work attitude, and employability - Alain Cohn; Michel André Maréchal; Frédéric Schneider; Roberto A. Weber (University of Zurich, Department of Economics, 2015)
We study whether employment history can provide information about a worker's noncognitive skills - in particular about "work attitude", or the ability to work well and cooperatively with others. Our hypothesis is that, holding all else equal, a worker's frequent job changes can indicate poorer work attitude, and that this information is transmitted in labor markets through employment histories. We provide support for this hypothesis across three studies that employ complementary lab, field, and survey experiments. First, using a laboratory labor market in which the only valuable characteristic of workers is their reliability in complying with an employer's effort requests, we demonstrate that prior employment information allows employers to screen for such reliability and allows high-reliability workers to obtain better employment outcomes. Second, we conduct a field experiment in which we vary the frequency of job changes in fictitious job applicants' resumes. Those applicants with fewer job changes receive more callbacks from prospective employers. A third survey experiment with human resource professionals confirms that the resume manipulations in the field study create different perceptions of work attitude and that these account for the callback differences. Our work highlights the potential importance of job history as a signal of worker characteristics, and points to a cost for workers of frequent job changes.
Keywords: C90; C93; J01; E24; 330; Employability; Work Attitude; Job Mobility